The use of a cap-mounted tri-axial accelerometer for measurement of distance, lap times and stroke rates in swim training - Michaels, S.; Taunton, D. J.; Forrester, A. I. J.; Hudson, D. A.; Phillips, C. W. G.; Holliss, B. A.; Turnock, S. R. (Procedia Engineering, 2016)
This paper will report some of the findings from a trial which recorded accelerometer data from six elite level swimmers (three female and three male, varying primary event stroke and distance) over the course of a regular 15 week training block. Measurements from a head-mounted accelerometer are used to determine when the athlete is swimming, marking of turning points (and therefore distance and lap-time measurements), and is processed by frequency analysis to determine stroke-rate. Comparison with video where available, and with training plans and literature where not, have proven this method to be accurate and reliable for determining these performance metrics. The primary objective of this project was to develop a low-cost, simple and highly usable system for use in swim coaching, feedback from elite coaches has indicated that development of this could be an extremely useful addition to their training regime.